A new model for the analysis of quench in HTS cable-in-conduit conductors based on the twisted-stacked-tape cable concept for fusion applications. (7th May 2020) - Zappatore, A; Heller, R; Savoldi, L; Wolf, M J; Zanino, R
Abstract: Several new conductor designs for fusion applications, based on high temperature superconducting (HTS) materials, have been recently proposed worldwide. Most of them are based on the twisted-stacked-tape cable (TSTC) idea: a stack of HTS tapes is twisted, soldered and embedded in a copper tube, constituting what we identify here as a 'strand'. Few strands are then twisted around a central core to make an HTS cable. The cable is finally inserted in a stainless-steel jacket, which provides mechanical support and confinement for the forced flow of the supercritical helium coolant through the interstitials among the strands. The thermal gradients that build up in a TSTC make the 1D thermal-hydraulic models developed for low temperature superconducting magnets unsuitable to study fast transients such as quench propagation. A new model is presented here, which allows describing each strand, and separately accounting for the respective superconducting (SC) stack and copper tube. Compressible Euler-like equations describe the He flow and thermodynamic state in each interstitial fluid region. The distribution of the transport current is computed with a distributed parameter approach, self-consistently with the temperature distribution in the different so-called thermal components of the TSTC. The model is applied to the study of quench propagation in a conductor made of CroCo strands—a recent design proposed by the Karlsruhe Institute of Technology and based on the TSTC idea. A comparison with the modelling approach adopted for quench simulations in LTS conductors is carried out, showing that, when the heating is localized, the new model predicts, for the average temperature on the cross section at the hottest location along the conductor and for the voltage along the conductor, an evolution much slower than that predicted by a standard LTS-conductor model.